Лапароскопічна адреналектомія: досвід перших 300 операцій у клініці ендокринної хірургії - Черенько, С. М.; Ларін, О. С. (Clinical Endocrinology and Endocrine Surgery, 2010)
The clinical analysis of the first 300 laparoscopic adrenalectomies performed since 2003 presented in the article. Endoscopic approach operations have proved their advantages against conventional lumbotomy in all aspects, incl. spending time after sufficient learning curve. The possibility of successful removing of large tumors (up to 16 cm), noninvasive malignant primary tumors, solitary adrenal metastases, bilateral lesions, including bilateral pheochromocytomas has been evidently shown. Laparoscopic technique allows to perform resection of adrenal gland, simultant and diagnostic operations. Authors recommend scrutiny and insistence in training of experienced endocrine surgeons for wide implementation of laparoscopic adrenalectomy in surgical treatment of adrenal diseases.